Advances in geriatric oncology: a multidisciplinary perspective. Issue 4 (August 2018) - Somasundar, Ponnandai; Mourey, Loïc; Lozza, Laura; Maggi, Stefania; Stepney, Rob
A growing majority of people with cancer is composed of older patients. For many such patients, independence and quality of life are as important as prolongation of survival, emphasizing the need for treatments that are not only effective but also well-tolerated. Given age-related decline in organ function and the prevalence of comorbidities and polypharmacy, optimum management is complex and requires collaboration between oncologists and geriatricians. Advances in surgery now include preoperative assessment and, when indicated, prehabilitation of the patient, as well as the enhanced recovery after surgery approach. Medical treatment is benefiting from the advent of highly effective novel immunomodulatory agents that join the tumor-targeted small molecule tyrosine kinase inhibitors and monoclonal antibodies in modifying the tolerability of therapy. Improved tolerability is evident with radiotherapy (RT). The adoption of stereotactic body RT in community oncology practice is increasing the proportion of elderly patients with comorbidities who can receive curative treatment. A further aspect of precision medicine as it relates to the older cancer patient is the tailoring of intervention to the robustness or frailty and life expectancy of the individual. Quantitative and validated tools for comprehensive geriatric assessment are playing an important role in this process.